1999
DOI: 10.1002/jlb.66.6.915
|View full text |Cite
|
Sign up to set email alerts
|

Trp-Lys-Tyr-Met-Val-d-Met is a chemoattractant for human phagocytic cells

Abstract: Trp-Lys-Tyr-Met-Val-D-Met (WKYMVm) is a synthetic peptide that stimulates phosphoinositide (PI) hydrolysis in human leukocytes. The peptide binds to a unique cell surface receptor(s). Recently we had demonstrated that human neutrophils, monocytes, and B lymphocytes express this peptide-specific receptor and that stimulation of human leukocytes with the peptide leads to activation of the oxidative respiratory system and the bactericidal activity of neutrophils or monocytes. In this study we showed that the pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…Some viral chemokine homologues bind to chemokine or chemoattractant receptors, alter receptor activation properties, and inhibit the proper functioning of receptor-mediated immune responses (47). Because HIV T-20 peptide and H. pylori Hp (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) peptide are ligands of FPR and FPRL2, respectively, it appears that these pathogen-derived agonists suppress DC-mediated immune responses by activating FPR or FPRL2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some viral chemokine homologues bind to chemokine or chemoattractant receptors, alter receptor activation properties, and inhibit the proper functioning of receptor-mediated immune responses (47). Because HIV T-20 peptide and H. pylori Hp (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) peptide are ligands of FPR and FPRL2, respectively, it appears that these pathogen-derived agonists suppress DC-mediated immune responses by activating FPR or FPRL2.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that WKYMVm induces human monocytes and neutrophils to generate cellular superoxide and to undergo chemotactic migration (11)(12)(13). Three cell surface G-protein-coupled WKYMVm receptors have been identified (14 -16), namely, formyl peptide receptor (FPR), FPR-like 1 (FPRL1), and FPR-like 2 (FPRL2) (14 -16).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
“…A synthetic peptide, Trp-Lys-Tyr-Met-Val-D-Met, has been shown to be a chemotactic stimulus to phagocytic leukocytes including human monocytes (54). Even though the peptideinduced monocyte chemotaxis is pertussis toxin-sensitive, the peptide-specific receptor is different from receptors for MCP-1 and is insensitive to GF109203X.…”
Section: Discussionmentioning
confidence: 99%
“…WKYMVm has been reported to induce the chemotactic migration of phagocytic cells, such as monocytes and neutrophils (Bae et al, 1999b). Le et al (2000) demonstrated that WKYMVm induced cellular chemotaxis by binding to FPR.…”
Section: Effect Of the Wkymvm Analogs On Akt Phosphorylation In Fpr-ementioning
confidence: 99%